Microstructure and mechanical properties of highly porous Hastelloy-X nickel superalloy produced by a space holder approach - Aleksandra Bętkowska; Marcin Podsiadło; Adelajda Polkowska; Grzegorz Włoch; Wojciech Polkowski (Scientific Reports, 2025)
Abstract Highly porous nickel-based superalloys appear as attractive candidates to be applied e.g. as seals in gas turbine engines instead of honeycomb structures. Among various methods of producing open-porous materials, a space holder approach provides number of benefits regarding economic and ecological aspects of production. In this work, the pioneering results of microstructure and mechanical properties analyses of highly porous Hastelloy-X nickel superalloy produced by the space holder approach, are presented. The materials were fabricated by using spherical fine Hastelloy-X powders and carbamide particles as batch materials. A multi-step powder metallurgy and thermomechanical processing was applied to produce open porous samples having a total volumetric porosity of 50, 60 and 70%. The produced materials were subjected to non-destructive (X-ray computed tomography) and metallographic inspections. Mechanical properties of the porous Hastelloy-X samples were examined in static room temperature compression tests, to discuss the effect of obtained porosity on compressive response.